Aplikasi Manajemen Diri COPD sebagai Inovasi untuk Meningkatkan Kualitas Hidup Pasien Paru Obstruktif Kronis - Syafira Aulia Rahmah (Jurnal Studi Inovasi, 2022)
Chronic obstructive pulmonary disease is one of the main causes of morbidity and mortality that has an impact on public health problems. This will affect the quality of life COPD patients. The prevalence of COPD patients in the world in 2016 was reported as 251 million cases, of which 3.17 million died. Some of the symptoms experienced by COPD patients are shortness of breath, chronic cough (>2 weeks), cough with phlegm, breath accompanied by wheezing, and some non-specific symptoms are lethargy, weakness, insomnia, and depression. Quality of life is related to health status which reflects the impact of individual health on functional well-being. Identifying predictors for health-related quality of life can provide deep insights into treatment and care strategies. The data used in this study came from various literatures related to problems discussed. Pulmonary rehabilitation interventions are well known in the treatment of patients with COPD and are an effort to increase activity capacity and quality of life of COPD patients. TRAINER COPD is an mHealth (mobile health) design that is integrated into a smartphone the contains medical care for patients. The most commonly used mHealth application is the use of smartphones to provide education about health problems and how to prevent them for users.